Effect of Arnebia euchroma ointment on post-laser wound healing in rats. (February 2015) - Aliasl, Jale; Barikbin, Behrooz; Khoshzaban, Fariba; Naseri, Mohsen; Sedaghat, Reza; Kamalinejad, Mohammad; Talei, Daryush; Emadi, Fatemeh; Akbari, Zahra; Aliasl, Fatemeh; Jalaly, Niloofar Y.; Mohseni-Moghaddam, Parvaneh
Abstract Introduction: Arnebia euchroma ointment has been used in Iranian Traditional Medicine for burn wound healing. The aim of this study is to evaluate wound healing efficacy of A. euchroma ointment on wounds induced after fractional CO2 laser in rats. Material and methods: In this study, after anesthetizing two bilateral burn wounds were induced on dorsal skin of the rat using fractional ablative CO2 laser. After applying laser, A. euchroma ointment, petrolatum, and silver sulfadiazine cream were used topically on wounds twice daily for 10 days. Digital photographs were captured from the wound surfaces every day. At the end of the study, two blinded dermatologists observed the photograph of 3rd, 5th, 7th, and 9th days after laser injury and assessed erythema, crusting/scabbing, epithelial confluence, and general wound appearance to determine the efficacy of wound healing. These wound-healing parameters were assessed using the 5-point scales. Results: This study showed significantly less erythema and crusting (P = 0.024 and P = 0.004, respectively) on 9th day and higher epithelial confluence and general wound appearance scores on 7th (P = 0.037 and p = 0.016, respectively) and 9th days (P = 0.008 and P = 0.016, respectively) in A. euchroma ointment compared with other groups. Conclusion: This study showed A. euchroma ointment has good healing effects on post-laser wounds in rats.